Are filtered plasma proteins processed in the same way by the kidney?. (7th December 2016) - Comper, W.D.; Russo, L.M.; Vuchkova, J.
Abstract: In order to understand the mechanism of albuminuria we have explored how other plasma proteins are processed by the kidney as compared to inert molecules like Ficolls. When fractional clearances are plotted versus protein radius there is a remarkable parallelism between protein (molecular weight range 30–150 kDa) clearance in healthy controls, in Dent's disease, in nephrotic states and the clearance of Ficolls. Although there are significant differences in the levels of fractional clearances in these states. Dent's disease results in a 2-fold increase in the fractional clearance of proteins as compared to healthy controls whereas in nephrotic states there is a further 3-fold increase in fractional clearance. Previous thinking that albumin uptake was controlled primarily by the megalin/cubilin receptor does not explain the albumin urinary excretion data and is therefore an incorrect concept. Protein clearance in nephrotic states approach the fractional clearance of inert Ficolls for a given radius. It therefore appears that there are two pathways processing these proteins. A low capacity pathway associated with megalin/cubilin that degrades filtered protein (that is inhibited in Dent's disease) and a high capacity pathway that retrieves the filtered protein and returns it to the blood supply (without retrieval nephrotic protein excretion will occur and this will account for hypoproteinemia). On the other hand low molecular weight proteins (<20 kDa) are processed entirely differently by the kidney. They are not retrieved but are comprehensively degraded in the kidney with the degradation products predominantly returned to the blood supply. Highlights: Albumin processing by the kidney appears very similar to other plasma proteins in the molecular weight range 30–150 kDa. Proteins with molecular weight <20 kDa are processed in an entirely different manner. The enormous changes in protein clearance in nephrotic states can be explained by inhibition of both the degradation and retrieval pathways.